Behavior-based price discrimination in the domestic and international mixed duopoly - Suzuka Okuyama (Osaka University, Institute of Social and Economic Research (ISER), 2022)
This study investigates mixed markets in which a social welfare-maximizing public firm and a private firm engage in behavior-based price discrimination (BBPD). Total of two cases are considered: one where domestic shareholders completely own the private firm and one where foreign shareholders completely own it. In the domestic mixed duopoly, BBPD is irrelevant from the viewpoint of social welfare. This is because poaching does not occur. In the international mixed duopoly, BBPD improves domestic social welfare, as it allows the public firm to lower its poaching price. In both cases, privatization is more undesirable under BBPD than uniform pricing.
Keywords: D43; H42; L13; 330; Behavior-based price discrimination; Mixed oligopoly; Foreign firms; Privatization